Efeito da fonte de luz e da abertura de boca na fotoativação de resinas bulk fill em molares - Moreira, Rodrigo José (2019)
The aim of this study was to evaluate the influence of light source type and mouth opening dimension on the photoactivation of high viscosity bulk fill resins in lower second molar class II cavities. Eighty human molars received MOD cavity preparations with 3/5 of the intercuspal distance and 4mm depth in the occlusal box and 5mm in the proximal boxes and were divided into 8 groups formed by the 3 factors under study (light source - 2 levels; mouth opening - 2 levels and bulk fill resin - 2 levels). The teeth were restored with high viscosity bulk fill composite resin (Opus Bulk Fill APS, FGM or Filtek Bulk Fill One, 3M-ESPE) employing two light sources with different designs: straight body (VALO Cordless, Ultradent) and angled body ( radii-Cal, SDI). To simulate the interincisal opening, a mouth opening control system was developed, allowing two mouth opening conditions: limited (25 mm) and normal (45 mm). The teeth were subjected to thermal fatigue for 10,000 cycles at 5 - 55o C and mechanical fatigue by 50N occlusal loading for 1,200,000 cycles at a frequency of 2 Hz. The teeth were sectioned in the mesio-distal direction, and after polishing the teeth, the degree of conversion (DC,%) were measured in the mesial and distal proximal boxes and in the occlusal box at the same depth (n = 5). Dissolution of unpolymerized monomers was evaluated and standardized images were obtained before and after immersion for 24 hours in tetrahydrofuran. Marginal infiltration with silver nitrate was evaluated by scanning electron microscopy. DC data were analyzed by 3-way analysis of variance followed by Tukey's test (α = 0.05).Results: Values of% DC of VALO Cordless photoactivated restorations were not influenced by resin type or mouth opening, while values for radii-cal photoactivated restorations were influenced by resin type, aperture. The radii-cal light source caused greater difficulty in 6 positioning at the smallest mouth opening, showing a reduction in irradiance emission and light spectrum with the depth of the cavity. Monomer dissolution was minimal in most of the samples tested, although samples constructed with radii-cal light source and 25 mm mouth opening showed slightly increased dissolution. Conclusions: Light sources with angled body provide less irradiance to the proximal cavities of posterior teeth, resulting in worse performance in the activation of bulk fill resins in the proximal boxes. In the 45mm mouth opening the light sources did not influence the performance of composite resins.